Antioxidants and Lipids Peroxidation Status in Patients with Colon Cancer - Hassan Ali, Zahraa; Hadi Al-Saadi, Narjis (International Journal of Engineering and Technology, 2018)
Colon cancer is still one of the leading causes of cancer death worldwide and the second most common cause of mortality from cancer. It is caused by many factors such as hereditary, environmental, and dietary factors and insufficiency of physical activity. This study included fifty patients with colon cancer (21 female and 29 male) their ages ranging from 20 to 70 years old. Those patients were enrolled from Al-Hussain Medical City/Kerbala, and 33 healthy subjects who were free from signs and symptoms of cancer their ages were matched with cancer patients as a control group. Reduced glutathione, catalase, malondialdehyde and ceruloplasmin oxidase were measured in sera of those patients and the control group. The results showed a highly significant decrease (p = 0.0001) in reduced GSH levels and a highly significant increase (p = 0.0001) in the concentration of MDA in sera of colon cancer patients compared with the control group, whereas CAT and Cp oxidase activity did not show a significant difference. The demographic study revealed a significant decrease (p < 0.001) in the activity of CAT and a significant increase (p = 0.05) in the level of MDA in male patients comparing with the female group. The results of this study indicate that free radicals and antioxidants play an important role in colon cancer.Â Â